Chemical characteristics during the fermentation process of siam kintamani orange peel (Citrus nobilis) probiotic drink - Nadya Treesna Wulansari; A.A Istri Mas Padmiswari; Putu Rima Sintyadewi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
Functional foods containing bacteria that may improve digestive function are called probiotic beverages. The fruit is rich in vitamins, minerals, antioxidants, and bioactive substances that benefit the body's health. Therefore, it can be used to make non-dairy probiotic drinks. Kintamani is a province in Bali that produces fruit, namely Siam oranges. In 2021, citrus fruit production in Kintamani, Bangli, is the second highest, at 104,528 per ton. However, there are still damaged fruits due to poor post-harvest processing and management. Orange peel is one of the citrus wastes that is not utilized, but this waste can still be processed into food with good nutritional value. The skin of Siam oranges contains secondary metabolites composed mainly of flavonoids, phenols, steroids, and triterpenoids. Furthermore, the Kintamani orange peel has better antioxidant potential than its seeds. Metabolites derived from Siam Kintamani orange peel have the potential to be used as probiotic beverages. A SCOBY (Symbiotic Culture of Bacteria and Yeasts) starter produces Siam orange peel probiotic drink. SCOBY is a gel layer formed from a mixture of bacteria and yeast. The desired outcome of this study was to assess the total acid, degree of acidity, pH, vitamin C, and total reducing sugar of Siam Kintamani orange peel as a result of fermented probiotic drinks. This is an experimental study with an entirely randomized approach. The treatment in this study was a variation in fermentation length, including several days (0, 3, 6, 9, 12, 15, and 18 days), with 4 repetitions. ANOVA was used to analyze the data, followed by a multiple-range test based on Duncan's equation, the fermentation time had a substantial impact on the total acid, pH, vitamin C, and total flavonoids of the Siam Kintamani orange peel probiotic drink (Citrus nobilis) (p<0.05). The time of the fermentation process influences the entire amount of acid, pH, vitamin C levels, and quantity of flavonoids in the Siam Kintamani orange peel probiotic drink. The longer the fermentation process, the more the total acid value increases while the pH decreases. The highest content of vitamin C and total flavonoids was produced on the ninth day of fermentation, at 70455.33 mg/100 ml and 25.46 mg QE/100 g, respectively.